İZOLE PERFÜZE SIÇAN BÖBREĞİNDE ADENOZİN'İN GLOMERÜLER FİLTRASYON VE PERFÜZYON BASINCINA ETKİLERİ - AKBAŞ, Nurten; KÜÇÜKHÜSEYİN, Cihat (Cerrahpaşa Medical Journal, 2019)
Background. Renal effects of adenosine seem to be rather complex and likely to be mediated by differing mechanisms, some of which needs still further elucidation. So, it was of interest to see the effects of adenosine applied into the renal artery by infusion rather than by bolus injection under constant perfusion rate and to explore its interaction with theophylline and quinidine. Design. Adenosine (10 mg/ml) was applied into the renal artery at a constant rate for 15 min, during which perfusion pressure and rate of urine production as number of drops/10 min was continuously recorded. The interaction of adenosine with theophylline (1mM), a P1Purinoceptor antagonist and quinidine (2mg/ml), a P2purinoceptor antagonist, was studied by appliying adenosine in the presence of these agents. Results. Intrarenal perfusion of adenosine caused a biphasic vascular response, e.g. an initial pressory phase followed by a depressory one, during which urine production tended to reduce nonsignificantly. The pressory effect of adenosine was fully antagonized by theophylline with no remarkable effect on depressory one. Quinidine was, however, almost ineffective on these parameters or caused some potentiation. Reduction of urine production by adenosine was readily responsive to blockade by these purinoceptor antagonists. Perfusion pressure and urine production were increased in a perfusion ratedependent manner. Under different perfusion rate, the biphasic vascular effect of adenosine appeared to be rather identical and urine production was not effected markedly. Conclusion. From these results, it was concluded that application of adenosine by infusion modifies receptor affinity for purinoceptor antagonists in such a way that receptors mediating vasoconstriction become unavailable for the antagonists and those responsible for vasodilation was responsive to occupation with theophylline. Antagonism of the inhibitory action of adenosine on urine production by the antagonists was considered as evidence for the involvement of P1as well as P2purinoceptors in this process.